New species of flea-toad, genus Brachycephalus (Anura: Brachycephalidae) from the Atlantic Forest of Espírito Santo, Brazil - Almeida-Silva, Diego; Silva-Soares, Thiago; Rodrigues, Miguel Trefaut; Verdade, Vanessa Kruth (Zootaxa, 2021)
We describe a new species of dull-colored flea-toad, genus Brachycephalus, from the Atlantic Forest of Caparaó mountains in southeastern Brazil. The new species is characterized by its diminutive size, “leptodactyliform” body, brownish color with an inverted V-shaped dark mark on dorsum, skin smooth, hyperossification and dorsal shield absent, linea masculinea absent, Fingers I and IV vestigial, Toe I externally absent, Toe II reduced but functional, Toes III and IV with pointed tips, Toe V vestigial, and ventral color uniformly brown. It is a leaf litter dweller, known only from type locality in the humid forests on the eastern slopes of Parque Nacional do Caparaó mountains, a protected area in the states of Espírito Santo and Minas Gerais, southeastern Brazil. It is the third flea-toad occurring in the state of Espírito Santo recovered as sister to all other Brachycephalus distributed from the state of São Paulo northward in the Atlantic Forest.